The Roles of Store Atmosphere in the Consumer Buying Behavior - Anâ€™nisa, Vita; H Ahmad, Suryana; Hidayat, Rahmat (International Journal of Engineering and Technology, 2019)
This article presents a store atmosphere created through the exterior, general interior, store layout and interior displays and their influence on consumer buying behavior. The object of this study was Little Wings CafÃ©, one of the most-visited cafes in Bandung, Indonesia. This cafe is designed with a library and home theme like a Barbie house. This study employed the quantitative research method using descriptive statistics. A total of 100 samples were collected from a population of 2,310 visitors. The analysis results showed that store atmosphere has a positive influence for buying decision, in which the consumers were mainly attracted by the unique outside design. In addition, the consumers have a high tendency to visit a cafe which can make their mood better and they search for information about cafes prior to visitingÂ